Annual book of ASTM standards 2006 : Section 5, Petroleum products, lubricants, and fossilfuels - American Society for Testing and Materials (West Conshohocken, PA : American Society for Testing and Materials, 2006)
Contents : v. 5.01 - Petroleum products and lubricants (1) -- v.5.02 - Petroleum products and lubricants (II) -- v.5.03 - Petroleum products and lubricants (III) -- v.5.04 Petroleum products and lubricants (IV) -- v.5.05 - Test methods for rating motor, diesel and aviation fuels ; catalysts; manufactured carbon and graphite products -- v.5.06 - Gaseous fuels; coal and coke
'Revision issued annually'